Sensitivity analysis and statistical process optimisation of deep drawing of AA 6061 sheet material. (1st May 2013) - Raju, S; Ganesan, G; Karthikeyan, R
<x xml:space="preserve">Abstract</x> Deep drawing, besides its importance as a forming process, also serves as a basic test for sheet metal formability. The elastic deformation within the overall amount of deformation is not desired and leads to springback in the drawn components. This affects the dimension and shape of the formed cups. Fundamental understanding of variation of the process parameters has become essential for accurate rapid design of tooling and processes in early design stage. Therefore, in the present study, the effect of parameters such as the die shoulder radius, punch nose radius and the blank holder force on the deep drawing of AA 6061 aluminium alloy is studied and mathematical model was developed using response surface methodology. The parameters were optimised for minimum springback. Sensitivity analysis was carried out to evaluate the effects of each process parameter on springback. The optimal values of die shoulder radius, punch nose radius and blank holder force for minimising the springback were found to be 3 mm, 3 mm and 6 kN respectively.